PERLINDUNGAN HUKUM BAGI PENGGUNA JALAN TERHADAP KEBERADAAN TIANG LISTRIK OLEH PT.PLN (Persero) AREA SAMARINDA DI JALAN BUNG TOMO SAMARINDA SEBERANG KOTA SAMARINDA” (DITINJAU BERDASARKAN UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JA - Jumintar Napitupulu (Universitas 17 Agustus 1945 Samarinda, 2014)
ABSTRACT Purpose of this study is order to knowing better the legal of road users regarding to the existence of an electric pole in the Bung Tomo street Samarinda Seberang ( Regulated by Law Number 22 of 2009 about the traffic and road transport). The research methodology used in this writing is judicial empiric with analytical descrivtive qualitative. The author deliberately the issu of legal protection of road user on the road law.Legal protection provided by the government through the Department of Public Works Government of East Kalimantan to road users in Samarinda Seberang Bung Tomo Street Samarinda city in terms of the tasks and functions as the principal organizer for the occurrence of road traffic congestion and accidents due to road users of road construction leaving a power pole on the shoulder of the road , given the form of providing protection to the victim insurance funds and according to the rules.In terms of legal protection as the title of this the relevant agencies either the Public Works East Kalimantan and PT . PLN ( Persero ) Samarinda area are expected to coordinate and synchronize the best execution of certain tasks this able to avoid either which hamper the smooth running of the program, work carried out by the relevant agencies as well as those undertaken by both parties ( contractors ) for the construction of Jl . SMD - SS ( Samarinda - Sanga Sanga ) by PT.PP - PAL , KSO which left a power pole on the shoulder of the road Jl . Bung Tomo pose a risk of traffic congestion so do traffic accidents . Keywords: Legal Protection, Road Users, Public Works